STRATEGI PENGEMBANGAN EKOWISATA DI KELURAHAN SEI GOHONG KECAMATAN BUKIT BATU KOTA PALANGKA RAYA - Theresya Fitriana; Lilis Hartati; Taufik Hidayat; Emmy Lilimantik (EnviroScienteae, 2019)
Ecotourism in Sei Gohong Village, Bukit Batu Subdistrict, Palangka Raya City, Central Kalimantan Province requires the appropriate concept of development strategy. SWOT analysis is employed to identify strengths, weaknesses, opportunities, and threats involved and to determine the development strategies that are required. The results of the SWOT analysis indicate that the most appropriate strategy is the WO strategy, which is a strategy that utilizes all opportunities to minimize weaknesses. The WO strategy consists of (1) Increasing various facilities to attract visitor’s appeal, (2) Making the riverbank tourism under good management, (3) Making various attractive packages for tourism, (4) Conducting training for tour guides, security officers and how to improve the additional value of Bawang Dayak for the local community, (5) Enhancing improvement for Pokdarwis in terms of management.